Peculiarities of Modern Latin American Regionalism - Besik Goginava (Advances in Social Sciences Research Journal, 2019)
The concept of Regionalism has gained a significant popularity in present-day international relations and political science. Besides attracting impressive attention as a form of economic, political and social organization since the World War II, in the 21st century Regionalism has evolved into a popular field of study too. Today Regionalism is multidimensionally defined. It is an ideology and political movement that focuses on the development of a particular region. In international relations Regionalism is transnational cooperation to achieve a common goal or resolve a mutual problem within a specific geographical region. It also refers to a group of countries that are linked by geography, history or economic characteristics, such as Latin America. Therefore Regionalism seeks to strengthen the ties between these nations, like the European Union. Regionalism in Latin America has a history going back to the revolutionary and post-colonial period. The leaders of the wars of independence envisioned the idea of creating united Latin American regional state or confederation, in order to protect their fragile independence out of European powers. Importantly, regionalism in Latin America has historically oscillated between the United States of America led and exclusively Latin American and integration projects.